Port Site Infiltration and Intraperitoneal Instillation of Bupivacaine for Post Operative Analgesia in Laparoscopic Cholecystectomy (Faridpur Medical College Journal, 2020)
Laparoscopic cholecystectomy has become the gold standard treatment method for symptomatic gallstone diseases. However pain is the only complaint that delays the discharge. This study aimed to evaluate the efficacy of bupivacaine infiltration into port site and instillation into peritoneal cavity to reduce pain following laparoscopic cholecystectomy. One hundred patients underwent elective laparoscopic cholecystectomy enrolled in this study. Patients were divided into experimental group (Group A) and control group (Group B) of 50 patients each. Following removal of gallbladder, patients of experimental group received 20 ml of 0.5% bupivacaine in gallbladder bed and 20 ml of 0.5% bupivacaine was infiltrated into 4 port sites. Control group received no treatment. The evaluation of postoperative pain was done at 4, 8, 12 and 24 hours postoperatively by using Visual Analogue Scale and the dose of NSAID was also recorded. Mean VAS score at 4, 8 and 12 hours postoperatively in experimental group was less than that of the control group (p0.05). The mean total NSAID doses used during first 24 hours postoperatively was less in the experimental group than control group (p